2021
DOI: 10.1002/psp4.12619
|View full text |Cite
|
Sign up to set email alerts
|

PBPK modeling to predict drug‐drug interactions of ivosidenib as a perpetrator in cancer patients and qualification of the Simcyp platform for CYP3A4 induction

Abstract: Ivosidenib is a potent, targeted, orally active, small-molecule inhibitor of mutant isocitrate dehydrogenase 1 (IDH1) that has been approved in the United States for the treatment of adults with newly diagnosed acute myeloid Leukemia (AML) who are ≥75 years of age or ineligible for intensive chemotherapy, and those with relapsed or refractory AML, with a susceptible IDH1 mutation. Accepted ArticleThis article is protected by copyright. All rights reserved Ivosidenib is an inducer of the CYP2B6, CYP2C8, CYP2C9,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Ivosidenib is a substrate and an inducer of CYP3A4 and also induces CYP2B6, and CYP2C enzymes. PBPK modeling was used to predict magnitude of CYP2B6, CYP2C8, CYP2C9, and CYP3A4 induction of ivosidenib along with other DDI predictions in patients with cancer 51 . For CYP3A induction prediction, the in vivo induction parameters were optimized using 4β‐hydroxycholesterol (4‐OHC), an endogenous biomarker of CYP3A4 activity, data being obtained from patients.…”
Section: Strong Cyp3a Inducersmentioning
confidence: 99%
“…Ivosidenib is a substrate and an inducer of CYP3A4 and also induces CYP2B6, and CYP2C enzymes. PBPK modeling was used to predict magnitude of CYP2B6, CYP2C8, CYP2C9, and CYP3A4 induction of ivosidenib along with other DDI predictions in patients with cancer 51 . For CYP3A induction prediction, the in vivo induction parameters were optimized using 4β‐hydroxycholesterol (4‐OHC), an endogenous biomarker of CYP3A4 activity, data being obtained from patients.…”
Section: Strong Cyp3a Inducersmentioning
confidence: 99%
“…According to the literature ( Upreti et al, 2011 ; Boulton, 2017 ), here, we assumed that all DPP-4 enzymes were located in the blood compartment in the present model. Across published studies ( Rowland Yeo et al, 2011 ; Bolleddula et al, 2021 ), k deg values of CYP3A4 ranged from 0.0077 –1 to 0.03 h −1 . However, a recent study has confirmed that it was a more reasonable value at 0.03 h −1 for the most accurate prediction ( Rowland Yeo et al, 2011 ); hence, the k deg value was set at 0.03 h −1 in this PBPK-DO model.…”
Section: Discussionmentioning
confidence: 98%
“…The CYP3A4 induction parameters of the default rifampicin model (maximal fold induction of CYP3A4 over vehicle [Ind max_CYP3A4 ] = 16, drug concentration that supports half maximal induction of CYP3A4 [IndC 50_CYP3A4 ] = 0.32, unbound fraction of drug in enterocytes [f u,gut ] = 1) have been validated extensively using clinical DDI studies with a large number of CYP3A4 substrates. 4,22,23 An alternative set of CYP3A4 induction parameters (Ind max_CYP3A4 = 30.6, IndC 50_CYP3A4 = 0.32, f u,gut = 0.116), which were previously used as a worst case assessment of DDI liability for metabolically stable CYP3A4 substrates, further improved the predictions for some compounds such as bosutinib by simulating a stronger induction of CYP3A4 (Figure S7). Although bosutinib is predominantly metabolized by CYP3A4 (f m,CYP3A4 ≈ 1), such improvement should be interpreted with caution as rifampicin is also shown to induce other proteins such as CYP1A2, CYP2B6, CYP2C8, CYP2C9, UDP glucuronosyltransferase (UGT)1A1, and possibly organic anion transporting polypeptide (OATP)1B1, 15,[43][44][45][46][47][48] which may account for the underestimation of DDIs with the default rifampicin model when their involvement, if any, is not considered in the substrate model.…”
Section: Discussionmentioning
confidence: 99%
“…was a 1.4-fold to 3.5-fold increase in P-gp protein levels in healthy subjects who received 600 mg rifampicin once daily for 10 days, as measured using immunohistochemistry and Western blot. 16 Although the application of PBPK in predicting CYP3A4 induction has been well established, 4,22,23 the use of PBPK in predicting P-gp induction is relatively less reported. The published PBPK models for rifampicin incorporated the measured fold increase in the P-gp protein level and reasonably recovered the clinically observed magnitudes of DDIs with a number of P-gp substrates (e.g., digoxin and talinolol) when coadministered with rifampicin.…”
Section: How Might This Change Drug Discovery Development And/or Therapeutics?mentioning
confidence: 99%
See 1 more Smart Citation